Grounded Theory Analysis on IT Consultant Company Survival Strategy in The Vuca Era - Fauzan, Heri; Heikal, Jerry (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research was focused on how IT Consulting Companies can survive during the VUCA era (within scope 2020-2023). This research revealed the challenges during the VUCA Era and strategies to tackle the challenges. This research was conducted using grounded theory analysis, interviewing process, and gap analysis with the current theories. All methods are compiled together as a qualitative research approach. In this research, purposeful sampling was used to choose relevant respondents with minimum classification as a director level in an IT Consulting Company who knew about the company strategy and business environment during the in-scoped period. The coding process was done twice, the first coding process to map the challenges in the VUCA era and the second one to find out the strategy for VUCA challenges in the first coding results. The coding process gathered 23 codes for challenges in VUCA which were categorized into 9 categories and then became 5 themes. The result concludes that the top challenge in the VUCA era is customer engagement. The second coding process found the 23 strategies from all interviews and categorized them into 5 categories and then 4 themes. It concludes that the top priority strategy to survive during VUCA is a customer-driven approach strategy with many variations.